(3BOGH GdeQjOs - (3GdehUdj , YHO Gddg Hf Ydj Hf YHO Gddg GdTjHGfj, CHh HcQ,J (B820 (3g` s
(3ChdgG (B:s
(3hHYO agPG cJGH GfJbjJI ef cdGe Cgd GdJUha jfJaY Hg GdeHJOF hjJPcQ Hg WQjb Gdbhe Cgd GdJUha s
(3BNQgG (B:s
(3CUM GdYbhd Ybd hGab GdJhajb hTQ GdWGYGJ WGYI JhQK YLHkG hNjQ GdPfhH PfH CYbHg JhHI hGddg CYde s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B91s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JUha JjehQ (B2929) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs